2018
DOI: 10.3389/fmicb.2018.01403
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Segmented Filamentous Bacteria in Human Children and Its Potential Role in the Modulation of Human Gut Immunity

Abstract: Segmented filamentous bacteria (SFB) are commensal organisms that grow by anchoring a specialized holdfast structure to the intestinal walls of a variety of animals. Interaction of SFB with Peyer’s patches in mice promotes the post-natal maturation of the immune system. We previously reported that the colonization of SFB in humans mainly occurs by 36 months of age, and is difficult to be detected afterward. In this study, we measured the level of SFB in intestinal fluids of human children. SFB were found via q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 39 publications
0
71
0
1
Order By: Relevance
“…SFB antigen‐specific T H 17 cells have been identified in SFB colonized mice, whereas nonspecific T H 17 cells were induced in Peyerʼs patches, isolated lymphoid follicles, and the spleen . Clinical studies have shown that SFB colonization in humans primarily occurs by 36 months of age, and the presence of SFB in terminal ileal biopsies induced T H 17 pathway genes …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SFB antigen‐specific T H 17 cells have been identified in SFB colonized mice, whereas nonspecific T H 17 cells were induced in Peyerʼs patches, isolated lymphoid follicles, and the spleen . Clinical studies have shown that SFB colonization in humans primarily occurs by 36 months of age, and the presence of SFB in terminal ileal biopsies induced T H 17 pathway genes …”
Section: Introductionmentioning
confidence: 99%
“…(30) Clinical studies have shown that SFB colonization in humans primarily occurs by 36 months of age, and the presence of SFB in terminal ileal biopsies induced T H 17 pathway genes. (24,31) SFB has immunomodulatory actions regulating the development and homeostasis of host tissues, both locally in the gut (20,21,32) and at extra-GI sites. (33)(34)(35) SFB promotes T H 17/ IL17A-mediated immunity, (20,21,(28)(29)(30) which has been shown to aggravate autoimmune conditions distant to the gut.…”
Section: Introductionmentioning
confidence: 99%
“…When comparing our k‐medoids results to our microbial pathogen sequence correlation data, we also observed that the RBC antigen immunogenicity clusters followed a trend similar to our immunogenicity‐microbial genera correlation, raising the question of a mechanistic link. Exposure to environmental pathogens and commensal bacteria has long been implicated in shaping our immune systems in the formation of ABO‐group antibodies, and more recently to the development of antigen specific Th17‐type immune responses in mouse models of autoimmune disease, as well as a potential role in humans . These serve as just a few examples of how surrounding microbes interact with and shape our immune responses, and highlight the importance of examining this potential relationship in a prospectively‐designed, future experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Increased SFB levels are associated with enhanced disease severity in a number of autoimmune disorders. SFB are also found in humans, but only in an age-dependent manner [27] and in low abundance. In humans, SFB enhance immune responses, including sIgA production and Th17 induction, and activate T and B cell signaling.…”
Section: Commensal Bacteria and Their Positive Influence On Healthmentioning
confidence: 99%
“…In humans, SFB enhance immune responses, including sIgA production and Th17 induction, and activate T and B cell signaling. This indicates that SFB play an important role in modulating the immune system in early life [27]. …”
Section: Commensal Bacteria and Their Positive Influence On Healthmentioning
confidence: 99%